Open to critique: predictive effects of academic outcomes from a bridging/foundation programme on first-year degree-level study. Issue 1 (2nd January 2017) - Curtis, Elana; Wikaire, Erena; Jiang, Yannan; McMillan, Louise; Loto, Robert; Fonua, Sonia; Herbert, Rowan; Hori, Melissa; Ko, Teri; Newport, Rochelle; Salter, David; Wiles, Janine; et al.
Abstract : Bridging/foundation programmes are often provided by tertiary institutions to increase equity in access and academic performance of students from under-served communities. Little empirical evidence exists to measure the effectiveness of these bridging/foundation programmes on undergraduate academic outcomes. This research identifies the predictive effect of academic outcomes achieved within a bridging/foundation programme, targeted towards indigenous and ethnic minority students, on first-year degree-level outcomes. Overall performance within the bridging/foundation programme was positively associated with increasing Grade Point Average (GPA), 'Core 4' GPA and passing all courses in first year. However, mixed associations were identified between feeder bridging/foundation courses and their intended first year course counterparts. These findings support the continued provision of bridging/foundation education; however, curricular reform within the bridging/foundation programme was required. Key developments included: restructuring course delivery; increasing constructive alignment across the curriculum; increasing cultural content within western science-orientated courses; introduction of cross-curricular assessment and use of additional innovative teaching and learning activities. Additional challenges remain for degree programmes to explore how they can change in order to better support indigenous and ethnic minority student success within first-year tertiary study.